METHODS OF CORPORATE CAPITAL STRUCTURE OPTIMIZATION - FROLOV, SERHIY; DYKHA, MARIIA; DZIUBA, VIKTORIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
When forming the optimal capital structure, the choice of methods, approaches, tools is important, which is determined by a set of initial conditions, the need to perform the tasks, achieving results / strategic guidelines. The purpose of the article is to systematize scientific approaches to optimize the capital structure, to clarify the impact of factors on the capital structure of the corporation, which will serve as a basis for ensuring the optimal level of capital structure.As a result of the research, the views of scientists on the optimization of capital structure are systematized, the key aspects of the three main approaches to such optimization are singled out and described. The approaches used in determining financial leverage are described. The expediency of determining financial leverage through the ratio of EPS - earnings per share and EBIT - earnings before interest and taxes is substantiated. The most common methods of capital structure optimization are identified: the method of capital expenditures (the method of minimizing the weighted average cost of capital); the method of determining the effect of financial leverage or the method of maximizing the level of financial profitability; method of determining the complex operational and financial leverage; EBIT-EPS valuation method, Du Pont method, operating profit method and adjusted present value method. Their features, advantages and disadvantages of use are described. The factors influencing financial leverage are systematized, the positive or negative influence of each of the determined factors on financial leverage is determined. A matrix of factors that determine the optimal capital structure in terms of the environment (internal or external) and the implementation of financial policy (at the strategic or operational-tactical levels).
Keywords: financial policy; corporate capital; financial performance; financial leverage